The Change of Reporter Communication Process at News Production in Pandemic - Lokananta, Arbi Cristional (RSF Conference Series: Business, Management and Social Sciences, 2021)
Communication is a basic human activity. By communicating, humans can relate to each other both in daily life at home, at work, in the market, in society or wherever humans are. There is no human being who will not engage in communication. Communication is very important for human life. The development of human knowledge from day to day because of communication. Communication also forms a social system that needs each other, therefore communication and society cannot be separated.(Cangara, 2014) Researchers chose a media which was originally a magazine. Broadcastmagz-TV & Radio Magazine is the magazine that was chosen but has switched to online form or broadcastmagz.com is one of the companies that currently has many sectors in various fields, one sector that is very well known by the Indonesian people is the Online Media sector.(Magazine, n.d.) This change in media products is included in media convergence. Visual communication is turning to paperless. Convergence in the Big Indonesian Dictionary means the situation towards one meeting point, convergence, while the definition of convergence or convergence is literally two or more objects meeting or uniting at a point of concentration of eyes to a very close place. Convergence is the joining of traditional telecommunications media with the internet network at once. Convergence is a radical change in the handling, provision, distribution, and processing of all forms of information, whether visual, audio, data, and so on. (Suchroni, 2016)